Impact of diabetes mellitus on 2-year outcomes of Absorb BVS compared to Xience EES: a pooled analysis of the COMPARE-ABSORB and AIDA trial. (25th November 2020) - Gao, C; Kerkmeijer, L; Tijssen, R.Y.G; Kraak, R; Tijssen, J; Onuma, Y; Chevalier, B; West, N; Morice, M.C; De Winter, R; Smits, P; Wykrzykowska, J.J; et al.
Abstract: Background and purpose: Diabetes mellitus (DM) is associated with increased risk of cardiovascular events after percutaneous coronary intervention (PCI). To evaluate the impact of Absorb bioresorbable vascular scaffold (BVS) in patients with DM, we aimed to compare the 2-year outcomes of Absorb BVS versus 2nd generation drug eluting stents Xience (EES) by pooling diabetic patients treated with BVS or EES from two large, randomized controlled trial. Methods: Patients with medically-treated DM and treated by Absorb BVS in the COMPARE-ABSORB and AIDA trial were pooled for analysis. The primary efficacy outcomes measure was target lesion failure (cardiac death, target-vessel myocardial infarction or target lesion revascularization), and the primary safety outcome measure was device thrombosis at 2-year follow-up. Results: Out of a total 3515 enrolled subjects in the two trials, 913 were diabetics. Compared with the non-diabetic patients, those with DM were older, more often to have a history of hypercholesterolemia, chronic renal failure, stroke, hypertension, heart failure, peripheral vascular disease and previous PCI. At 2-years, target lesion failure occurred in 10.8% of BVS DM patients and 7.6% of EES DM patients (adjusted HR 1.43, 95% CI: 0.87–2.34, P=0.115). The 2-year rates of cardiac death (2.4% vs 1.6%, P=0.385), TV-MI (5% vs 1.6%, P=0.123) and TLR (7.8% vs 5.8%, P=0.416) showed not significant difference. The 2-year incidence of definite device thrombosis was 3.2% in Absorb BVS versus 0.7% in Xience EES (adjusted HR 4.77, 95% CI: 1.01–22.43, P=0.048). Conclusion: This pooling of the diabetic patients from two large scale RCTs compared BVS versus 2nd generation DES, showed an increased rate of device thrombosis in BVS-treated patients at 2 years. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Abbott